Exergy study of air-conditioned space of a prototype scale of a river vessel room (2016)
The study was conducted on a scale prototype, which simulates one of the rooms in the real vessel air conditioning system. The main results are as follows: the higher the thermal load, the higher the exergy destruction, and increasing the average temperature in the room increases the exergetic efficiency and reduces the exergy destruction. There is an optimal thermal load per unit area of 214.074 W/m2. The highest exergetic efficiencies and lowest values of the exergy destruction indices occur when the average temperature of the room is in the comfort range recommended by ASHRAE, from 22 to 24°C. Copyright © 2016 by ASME.